Potret Perempuan Urban dalam Novel Divortiare Karya Ika Natassa: Kajian Sosiologi Sastra - Wan Elmira Islamay; Nurizzati Nurizzati (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
This study aims to: (1) describe the portrait of urban women in the Divortiare about the prestige of recreation, (2) describe the portrait of urban women in the Divortiare about the culture of instant living, (3) describe the portrait of urban women in the Divortiare about the mobility lifestyle, (4) describe the portrait of urban women in Divortiare about the individualist lifestyle. The object of this research is the novel Divortiare by Ika Natassa which was published in 2008. This research is literary research using descriptive methods. The data of this research are in the form of words, phrases, clauses, and sentences that show the prestige of recreation, instant living culture, mobility lifestyle, and individualist lifestyle in Ika Natassa's Divortiare. The research instrument is the author himself with the help of another instrument in the form of a recording sheet. Data collection techniques are reading and understanding novels, conducting library research, determining the main character, and finding and recording data related to research problems contained in the novel. The Data validation technique is using triangulation technique. The data analysis technique is identifying and classifying the data. Then interpret the data, and conclude the data analysis. The results of the study stated that (1) the recreational prestige of urban female characters in Ika Natassa's novel Divortiare can be seen through education, work, shopping, restaurants visited, and places of entertainment visited, (2) the instant lifestyle of urban women depicted in the novel Divortiare by Ika Natassa. Ika Natassa can be seen from people in their daily lives such as eating at fast food restaurants and online shopping, (3) the mobility lifestyle of urban women in Ika Natassa's Divortiare novel is seen from people who move around due to work demands, (4) portrait style The individualist life of an urban woman in the novel Divortiare by Ika Natassa is someone who does everything independently and chooses to live alone without the help of others.